A general C-glycosidation procedure via anomeric oxygen to carbon rearrangements of tetrahydropyranyl ether derivatives - Buffet, M; Dixon, D; Edwards, G; Ley, S; Tate, E (1997)
Lewis acid catalysed oxygen to carbon rearrangements of tetrahydropyranyl ether derivatives affords a new route to the corresponding 2-alkyl-substituted products.